Sources of value creation in China's iron and steel industry using dynamic panel data estimation - Ang, Jen Keng (2008)
The objective of this study is to find out the sources of value creation among 100 Chinese firms in the iron and steel industry during the period 1990 to 2000 using dynamic panel data estimation.